Biostimulants action in common bean crop submitted to water deficit - Galvão, Ícaro Monteiro [UNESP]; dos Santos, Osvaldir Feliciano [UNESP]; de Souza, Mara Lúcia Cruz [UNESP]; de Jesus Guimarães, João [UNESP]; Kühn, Irineu Eduardo [UNESP]; Broetto, Fernando [UNESP] (Elsevier, 2019)
The water deficit (WD) is one of the severe problems in agriculture resulting in yield loss. The understating of crops behavior face to this condition becomes of great importance, and the use of biostimulants may act as a vegetal growth-promoting, considering its capacity of attenuate the impacts of WD on plants. This study aimed at evaluating the common bean changes in biometric parameters and its yield supplemented with biostimulants, as a response to the imposition of WD. The assay was conducted in a protected environment in Botucatu, Brazil, with common bean cv. IAC Imperador, disposed in split-plot in randomized blocks, with 4 repetitions. The treatments in the plots correspond to the irrigation depths (10 kPa and 40 kPa) and in the subplots the treatment B1 (control); B2 (Bacillus amyloliquefaciens BV 03) and B3 (Bacillus amyloliquefaciens BV 03 + brown algae extract – Ascophyllum nodosum). The irrigation was by drip and the management using a tensiometer. The biometric variables included stem diameter; leaf number and leaf area; leaf dry mass, stem, root and total; root length, diameter and volume; and yield parameters. Discussing the results, it was possible to conclude that the common bean is a very water dependable crop, with WD imposition interfering in all the studied variables, with growth decrease, biomass accumulation and yield. The applied biostimulants (B2 and B3) presented low capacity to attenuate the WD effects in common bean under the cultivation conditions adopted.
Keywords: Drought stress; Growth-promoting bacteria; Irrigation management; Phaseolus vulgaris L.